"Miss having in-person classes" - university studying during COVID-19 pandemic - I. P. Visković (Russian State Vocational Pedagogical University, 2021)
Introduction. Managing the formal education system during COVID-19 has become an unwanted challenge for the academic community. Without suffi time for preparations, different models of distance education were applied. The aim was to ensure the continuity of teaching, to encourage the process of distance learning, and to enable their evaluation.Aim. This study aimed to analyse the opinions of students from the Department of Early Childhood Education (hereafter ECE) at the Faculty of Humanities and Social Sciences (hereafter Faculty), University of Split, on their study conditions during the COVID-19 from March 2020. It was assumed that learning in an online environment encourages the development of new learning strategies. Family and work status and residence of students (in the place of study or outside it) were taken as predictor variables in assessing the quality and conditions of the study.Methodology and research methods. The research was conducted online at the end of the 2020 academic year when students gathered online teaching experiences. The Google Apps tool was used in the data collection process. The Ethics Committee of the Faculty at the University of Split gave its consent to the implementation of this research. During online teaching, all students are informed about the purpose and course of research. Research included 68,75 % students (n = 156) studying at the ECE Department. The following aspects were investigated: forms and frequencies of distance learning; the possibility of students' response to study obligations (due to closed libraries); difficulties, advantages and possibilities of conducting online teaching; students' dissatisfaction with the quality of the organisation and implementation of online teaching, and opportunities for quality development.Results. Findings identified difficulties in the lack of ICT competencies of both students and teachers, mixed-use of different platforms, workload and lack of adequate literature. Students assessed the greater availability of teaching materials and more reachable teachers as positive, and experience of discussions on social networks as one of the useful ways of distance learning. By exchanging the content of teaching materials, they developed new learning strategies and showed possible new adaptations to learning using social networking. Students' dissatisfaction with online teaching could be interpreted by their subjective reasons and contextual conditions.Scientific novelty. The data processed in this research are triangulated with worldwide research on study conditions during lockdowns. It can be concluded that regardless of the previous lockdowns basic use of ICT (sending and receiving seminar tasks over e-mail), most higher education institutions were not ready for an overall transition to online teaching. The findings point to the need for systematic research into the possibilities of applying new technologies in the study process (learning, availability of relevant sources, networking of scientists, and quality exchange of information).Practical significance. Given that before the COVID-19 at this Faculty there was no similar research, nor experience with any online teaching forms, it is difficult to determine the extent of the change. Nevertheless, it is possible to conclude that the teaching staff did not have adequate ICT competencies for the implementation of quality online teaching. The quality of teaching in this research was contributed by more reachable teaching staff and their willingness to cooperate. In the changed living conditions as a consequence of the pandemic, it is possible to expect further changes in the way of studying. The insight and analysis of students' opinions through this research could contribute to the development of the quality of the teaching process in any given crisis.